Relatedness between samples quantified and an optimal criterion for match detection approximated - Gunnlaugsson, Thorvaldur (J. Cetacean Res. Manage., 2023)
Data on relatedness of individuals between or within samples can be used to address population parameters in much the same way as conventional mark-recapture data and has some advantages, but also opens up new research areas. In such studies not only decisions on the sample size have to be made but also the number of genetic markers to be worked up, or even developed, and during analysis the criteria for accepting a match chosen. The likelihood of detecting a true match must be assessed and weighed against the likelihood of including a false positive. To aid with this, formulae are presented here for the probability of the number of relatives alive over periods of time and a process to approach the optimal criterion for match detection. To apply the process programs were developed that are made available, and an example is given.